The influence of face angle and club path on the resultant launch angle of a golf ball - Wood, P.; Henrikson, E.; Broadie, C. (Proceedings, 2018)
A two-part experimental study was conducted in order to better understand how the delivered face angle and club path of a golf club influences the initial launch direction of a golf ball for various club types. A robust understanding of how these parameters influence the ball direction has implications for both coaches and club designers. The first study used a large sample of golfers hitting shots with different clubs. Initial ball direction was measured with a Foresight Sports camera system, while club delivery parameters were recorded with a Vicon motion capture system. The second study used a golf robot and Vision Research camera to measure club and ball parameters. Results from these experiments show that the launch direction fell closer to face angle than club path. The percent toward the face angle ranged from 61% to 83%, where 100% designates a launch angle entirely toward the face angle.